2017
DOI: 10.1002/jmri.25781
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐based assessment of acute effect of head‐down tilt position on intracranial hemodynamics and hydrodynamics

Abstract: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;47:565-571.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 29 publications
6
28
1
2
Order By: Relevance
“…There was also a decrease in SV, but it did not reach statistical significance. arterial inflow, increases in venous outflow, and no significant changes in CSF stroke volume or systolic velocity [12]. These observed changes in venous CSA under ground-based HDT are consistent with ultrasound studies performed during spaceflight that demonstrate comparable increases in venous CSA in subjects exposed to microgravity [23,24].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…There was also a decrease in SV, but it did not reach statistical significance. arterial inflow, increases in venous outflow, and no significant changes in CSF stroke volume or systolic velocity [12]. These observed changes in venous CSA under ground-based HDT are consistent with ultrasound studies performed during spaceflight that demonstrate comparable increases in venous CSA in subjects exposed to microgravity [23,24].…”
Section: Resultssupporting
confidence: 86%
“…Head-down tilt (HDT) has been used to simulate microgravity in ground-based studies that seek to quantify changes in arterial and venous flow dynamics. However, prior studies have yielded conflicting results about arterial blood flow dynamics [11,12] and have not comprehensively studied CSF flow dynamics, which is an important underlying aspect of the "fluids shift" hypothesis for SANS [8].…”
mentioning
confidence: 99%
“…A study using a 15° HDT protocol to assess venous jugular blood ow before, during, and after space ight on International Space Station crew members demonstrated that venous CSA increased from sitting to supine to HDT with a similar magnitude of change between those positions pre ight and post ight, although HDT in both of those settings overestimated increases in venous CSA found in-ight [32]. However, our venous and arterial changes from baseline to 15° HDT are corroborated by prior studies at these lower degrees of HDT, which lends support to the validity of our CSF ndings at 15° [10,11,36].…”
Section: Discussionsupporting
confidence: 86%
“…Ishida et al, using 15 healthy volunteers, found increases in venous CSA (36 mm 2 to 54 mm 2 ), decreases in arterial in ow, increases in venous out ow, and no signi cant changes in CSF stroke volume or systolic velocity [11]. These observed changes in venous CSA under ground-based HDT are consistent with ultrasound studies performed during space ight that demonstrate comparable increases in venous CSA in subjects exposed to microgravity, which lends validity to the results of these HDT protocols [23,24].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation